Women empowerment in Portugal: Realities, constraints, policies, strategies and initiatives - Vítor Jo\~ao Pereira Domingues Martinho (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
In Portugal we have yet problems with disadvantaged groups, in some cases because the social conditions, in other cases because the economic conditions and in another situations from the familiar and physical circumstances. This context sometimes is worse in the rural areas, because has other factors associated, as the alcoholism. So, is important to analyze these dynamics, write about those, propose some policies to interview and do something, namely for the women, which are yet in some situations a social group with disadvantages. In this line the objectives of this work is to present here some explanations and reflections about the Portuguese disadvantaged groups, referring some statistics available in some Institutions and analyzing profiles, and finally describe a project, as an example of social intervention, developed in rural counties in the center of Portugal with disadvantaged women, namely unemployed. In the final of this project was interviewed several persons and Institutions to understand their opinion about this initiative and all had a favorable judgment, what reflect the need and the importance of these social interventions. From here were proposed new social policies to be implemented in the Portuguese context that can help the public Institutions in the definition of the public strategies.
Keywords: O18; R00; Z13; 330; disadvantaged groups; rural areas; women empowerment